2021
DOI: 10.3390/pathogens10030368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Individual Viral Gene Segments from Influenza A/H5N8 Virus on the Protective Efficacy of Inactivated Subtype-Specific Influenza Vaccine

Abstract: Since its emergence in 2014, the highly pathogenic avian influenza H5N8 virus has continuously and rapidly spread worldwide in the poultry sector resulting in huge economic losses. A typical inactivated H5N8 vaccine is prepared using the six internal genes from A/PR8/1934 (H1N1) and the two major antigenic proteins (HA and NA) from the circulating H5N8 strain with the HA modified to a low pathogenic form (PR8HA/NA-H5N8). The contribution of the other internal proteins from H5N8, either individually or in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…NA H5N8+6PR8 vaccination indicated low protection capacity (less than 30%. 19,20 Similarly, the vaccine including both HA and NA (HA, NA H5N8+6PR8 ) segments were protective in our experiments, while the NAH5N8+7PR8 provided only 20% protection.…”
Section: Discussionsupporting
confidence: 60%
“…NA H5N8+6PR8 vaccination indicated low protection capacity (less than 30%. 19,20 Similarly, the vaccine including both HA and NA (HA, NA H5N8+6PR8 ) segments were protective in our experiments, while the NAH5N8+7PR8 provided only 20% protection.…”
Section: Discussionsupporting
confidence: 60%
“…It has been found that the HA of various avian influenza viruses contains multi-basic cleavage sites that are lethal to chickens, such as arginine (R) and lysine (K) sites in H5Nx and H7Nx [ 7 ], and REKRRKR/GLF in H5N8 [ 8 ]. After deleting the polybasic amino acids at the HA cleavage site of the HPAI parent virus, the new modified HA, along with the NA of the wild virus and the six internal segments of the backbone (such as A/PR/8/1934 H1N1 virus) is frequently used to generate a new low pathogenic virus as a vaccine candidate virus by reverse genetics (RG) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%